Perspectives on Cannabis-Based Therapy of Multiple Sclerosis: A Mini-Review - Mecha, Miriam; Carrillo-Salinas, Francisco J.; Feliú, Ana; Mestre, Leyre; Guaza, Carmen (Frontiers in Cellular Neuroscience, 2020)
The consistency, efficacy and safety of cannabis-based medicines have been demonstrated in humans, leading to the approval of the first cannabis-based therapy to alleviate spasticity and pain associated with multiple sclerosis (MS). Indeed, the evidence supporting the therapeutic potential of cannabinoids for the management of pathological events related to this disease is ever increasing. Different mechanisms of action have been proposed for cannabis-based treatments in mouse models of demyelination, such as Experimental Autoimmune Encephalomyelitis (EAE) and Theiler´s Murine Encephalomyelitis Virus Induced Demyelinating Disease (TMEV-IDD). Cells in the immune and nervous system express the machinery to synthesize and degrade endocannabinoids, as well as their CB1 and CB2 receptors, each mediating different intracellular pathways upon activation. Hence, the effects of cannabinoids on cells of the immune system, on the blood-brain barrier, microglia, astrocytes, oligodendrocytes and neurons, potentially open the way for a plethora of therapeutic actions on different targets that could aid the management of MS. As such, cannabinoids could impact the outcome of MS in terms of the resolution of inflammation or the potentiation of endogenous repair in the CNS, as witnessed in the EAE, TMEV-IDD and toxic demyelination models, and through other in vitro approaches. In this review, we summarize what is currently known about the peripheral and central effects of cannabinoids in relation to the neuroinflammation coupled to MS. We pay special attention to their effects on remyelination and axon preservation within the CNS, considering the major questions raised in the field and future research directions.